Defining a discovery: priority and methodological controversy in early nineteenth-century anatomy - Berkowitz, Carin (The Royal Society, 2014)
In the early nineteenth century, Charles Bell and François Magendie engaged in a decades-long priority dispute over the discovery of the roots of motor and sensory nerves. The constantly recalibrated arguments of its participants illuminate changes in the life sciences during that period. When Bell first wrote about the nerves in 1811, surgeon-anatomists ran small schools out of their homes, natural theology was in vogue, exchanges between British and French medical practitioners were limited by the Napoleonic Wars, and British practitioners typically rejected experimental physiology and vivisection. By the end of Magendie's career, medical science was produced in the laboratory, taught through artfully produced performances of the sort at which Magendie excelled, and disseminated through journals. It is not entirely clear which historical character, Bell or Magendie, ‘won’ the dispute, nor that they even had clear and consistent positions in it, but what is clear is that one style of science had won out over the other, and over the course of the dispute, pedagogy lost pride of place in medical science.